2020
DOI: 10.1021/acs.jpca.0c08979
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Ultrafast Dynamics of HD+ by the Carrier-Envelope Phases of an Ultrashort Laser Pulse: A Quasi-Classical Dynamics Study

Abstract: A theoretical study on the coupled electron-nuclear dynamics of HD + molecular ion under ultrashort, intense laser pulses is performed by employing a well-established quasiclassical model. The influence of laser carrier-envelope phase on various channel (H+D + , D+H + and H + +D + ) probabilities is investigated at different laser field intensities. The carrier envelope phase is found to govern the dissociation (H+D + and D+H + ) and Coulomb explosion channel (H + +D + ) probabilities. The kinetic energy relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Note that we have not considered the double-ionization channel [H 2 + + n ℏω → H 2 2+ + e] , in our dynamical calculations since it had previously been observed that after long time of propagation, this channel eventually explodes to form the Coulomb explosion products. It is worth to mention that by employing quasi-classical trajectory methods, the double-ionization channel can be properly counted when the diatomic bond length r bc < 9.5 bohr and the electron energy ε i > 0.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that we have not considered the double-ionization channel [H 2 + + n ℏω → H 2 2+ + e] , in our dynamical calculations since it had previously been observed that after long time of propagation, this channel eventually explodes to form the Coulomb explosion products. It is worth to mention that by employing quasi-classical trajectory methods, the double-ionization channel can be properly counted when the diatomic bond length r bc < 9.5 bohr and the electron energy ε i > 0.…”
Section: Resultsmentioning
confidence: 99%
“…We have employed a quasi-classical method based on Heisenberg’s model potential, which is quite well tested and has already been implemented in some of our previous studies on HD + and H 2 molecules. , Presently, we apply this model to a H 2 + molecular ion, which is a three-particle system consisting of two nuclei and one electron. The quasi-classical model is based on the Hamiltonian formulation of the classical mechanics, where the most crucial step is to define a total molecular Hamiltonian.…”
Section: Theoretical Foundation and Simulation Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The auxiliary potentials were first introduced by Kirschbaum and Wilets 40,41 and later, further developments were carried out by Cohen. 42 The model has been used extensively to study laser-driven atomic and molecular processes, 38,43–47 as well as atom–ion collision processes. 48…”
Section: Theoretical Model and Simulation Detailsmentioning
confidence: 99%
“…The auxiliary potentials were first introduced by Kirschbaum and Wilets 40,41 and later, further developments were carried out by Cohen. 42 The model has been used extensively to study laser-driven atomic and molecular processes, 38,[43][44][45][46][47] as well as atom-ion collision processes. 48 The field-free Hamiltonian of the H 2 molecule in the quasiclassical model is given by eqn (1) (atomic units are used throughout unless stated otherwise):…”
Section: Theoretical Model and Simulation Detailsmentioning
confidence: 99%